Malignant Melanoma With Neuroendocrine Differentiation: A Case Report and Literature Review - Cham, Jason; Shavit, Ayal; Ebrahimi, Aren; Viray, Miguel; Gibbs, Paul; Bhangoo, Munveer S. (Frontiers in Oncology, 2021)
Background Melanoma has a wide range of histologic variants and cytomorphologic features that make its diagnosis challenging. Melanoma can also rarely have neuroendocrine markers adding further diagnostic uncertainty particularly given that unrelated tumor types, such as prostate cancer, can also display focal neuroendocrine differentiations. Case presentation Our patient is a 74-year-old Caucasian man found to have a lung mass. Initial biopsy revealed typical microscopic morphology and neuroendocrine differentiation consistent with small cell carcinoma. Despite standard chemoradiation treatment, the patient continued to progress with new metastasis in the brain, liver and bone. Subsequent chest wall biopsy revealed golden-brown pigment associated with melanin. Further tumor immunohistochemistry revealed extensive neuroendocrine differentiation with CD56, synaptophysin, and INSM1, as well as strong immunoreactivity for melanocyte markers including SOX10, S100, PRAME, and MITF, consistent with metastatic melanoma with neuroendocrine differentiation. Genomic testing revealed increased tumor mutational burden and alterations in NF1, BRAF, CDKN2A/B, TERT. The patient was transitioned to checkpoint inhibitor therapy with nivolumab and ipilimumab and had resolution of his intracranial mass and decrease in size of other metastatic lesions. Conclusion Often the combination of anatomic findings such as a lung mass, typical microscopic morphology, and confirmation of neuroendocrine differentiation correctly identifies a patient with small cell carcinoma. However, in a patient who fails to respond to treatment, a broader immunohistochemical workup along with molecular testing with additional tissue may be warranted.